Strategi Manajemen Kurikulum dalam Pembinaan Karakter Religius Peserta Didik di Lembaga Pendidikan Islam: Studi Literature Review - Nadia Putri Kamila; sabila qurrota A'yun; Siti Musfiroh; Syifa Hanifah Syandra; Ahmad Fauzan (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study aims to analyze curriculum management strategies in fostering students’ religious character in Islamic educational institutions. The study employs a literature review method with a qualitative approach through the examination of various journal articles, scientific books, and academic documents relevant to the research theme. Data were collected through searches in Google Scholar, Garuda, DOAJ, and Scopus databases using keywords related to curriculum management, religious character, and Islamic education. Data analysis was conducted through the stages of data reduction, data classification, interpretation, and conclusion drawing. The results of the study indicate that curriculum management strategies in fostering religious character are implemented through habituation of religious activities, teachers’ role modeling, integration of Islamic values into learning processes, and the creation of a religious school culture. The implementation of curriculum management functions is carried out through the stages of planning, implementation, and evaluation of value-based religious education programs. These strategies have proven effective in improving students’ discipline in worship, responsibility, social attitudes, and spiritual awareness. However, the implementation of curriculum management strategies still faces several challenges, such as the influence of globalization, the development of digital technology, limited parental involvement, and the lack of optimal integration of religious values into all learning processes. This study contributes to the development of Islamic Education Management studies, particularly regarding curriculum management strategies based on religious character in Islamic educational institutions. Keywords: curriculum management, religious character, Islamic education, Islamic education management, literature review.